Design and Development of a Web-Based Tracer Study System in Higher Education Using the Waterfall Method (Case Study at Dian Nusantara University) - Priyanto, Mei Rendy; Ramayanti, Desi (Bahasa Indonesia, 2025)
This study aims to design and develop a web-based tracer study system at Dian Nusantara University using the Waterfall method. The system is designed to assist higher education institutions in tracking alumni's career paths and their level of satisfaction with the education they received. Additionally, this system aims to expedite the survey form completion process by alumni, ensuring that the collected data is more accurate and easier to analyze. The development stages include requirements analysis, design, implementation, and testing to ensure system performance. The outcome of this research is a platform that allows alumni to fill out surveys online, facilitating data processing by the university. This system is expected to strengthen the relationship with alumni and provide valuable information for curriculum development and educational planning.